PELATIHAN PENULISAN KARYA ILMIAH MENGGUNAKAN MODEL KLASIK - Rani Puspa Juwita; Iskandar Jalaludin; Ari Setyo Gumelar (Universitas Nahdlatul Ulama Lampung, 2017)
Teacher professional development is the activities of teachers in the context of practicing science, technology and skills to improve quality, both for the teaching and learning process and the professionalism of other education personnel and in order to produce something that is beneficial to education and culture. The professional development activities referred to are 1.) Making scientific papers / works in the field of education, 2.) finding technology in the field of education, 3.) making learning tools / teaching aids or guidance tools, 4.) Creating scientific papers, and participating in curriculum development activities (Ministry of National Education, 2001: 1). So writing scientific papers is an absolute requirement for teachers who will be promoted and certain groups. The making of scientific papers by teachers is still very limited in number. According to Zamroni, the Director of Based on the description above, it is considered necessary to conduct training activities in writing scientific papers for teachers, which due to limited time, energy and knowledge as well as the ability of teachers, are limited by elementary school teachers. The training was focused on increasing the willingness and ability (motivation) of teachers to write scientific papers in the form of papers, textbooks, modules and classroom action research. It is hoped that teachers will be productive in producing scientific papers. The method of this activity is in the form of training for teachers of SDN 1 Pulo Sari, Pasir Sakti, East Lampung. After being given further training they are guided to apply the results of the training in order to improve their professionalism and career. The following are the training stages. The implementation of these activities used several training methods, namely: the lecture method, the question and answer method, and the method of practice or practice. The final conclusion of the implementation of the community service program